Implementation of Gambling Laws in the First-Class City of Negros Occidental - Angeline E. Tangga (Philippine Social Science Journal, 1970)
Gambling poses significant harm to an individual and to society. This descriptive-comparative study assessed the extent of the implementation of Philippine gambling laws relative to cockfighting, card games, and lottery as assessed by 112 implementers, which included the police officers, Peace and Order Council (POC) chairpersons, and barangay captains of a first-class city of Negros Occidental. The data collected using a researcher-made questionnaire were analyzed using mean, t-test, and ANOVA. The findings of the study revealed that the extent of implementation of gambling laws in a first-class city as a whole, and when implementers are grouped according to designation and barangay categories is excellent. Moreover, the lottery was found to be of a considerable extent of implementation. A significant difference was noted in the extent of implementation when barangays are grouped according to category. Additionally, when implementers are grouped according to the designation, it was found that police officers significantly implement laws in cockfighting.